21st Century Maritime Power‐Politics in the Indian Ocean Region with Special Reference to the Bay of Bengal. (April 2017) - Karim, Mohd Aminul
Abstract: The aim of this paper is to project the emerging power‐relations in the maritime realm between geopolitical players in the Indian Ocean region. These power‐relations involve military shields and spears, infrastructure development, alignment–alliance relations, international trade routes, critical choke points, energy, and above all geopolitical implications. The methods followed in the paper are content analysis, case‐method, interview, observation, and so forth . The paper concludes that emerging power polarizations are visible and are gradually taking a tangible shape in the form of military–economic condominium, presumably coming from opposite directions.